The influence of pier height on the seismic isolation effectiveness of friction pendulum bearing for Double-Track railway bridges. (December 2020) - He, Weikun; Jiang, Lizhong; Wei, Biao; Wang, Zhenwei
Abstract: Friction pendulum bearing (FPB) is a sliding-based isolator, widely used in the seismic design of the bridge structure. However, there is neither unified standard nor complete evaluation system to evaluate the specific isolation effectiveness of FPB-isolated bridges with different pier heights. In this paper, the prototype bridge finite element models (FEM) of the typical simply supported girder bridges on the double-track railway in China, are established and studied. These bridge FEM differ in the pier height range of 4–60 m. Each FEM adopts two types of bearing: FPB (isolated bearing) and spherical steel bearing (non-isolated bearing). The nonlinear time history analysis is carried out to compare the seismic responses of FPB-isolated and non-isolated bridges. Based on the comparison results, the seismic isolation ratios of FPB are defined and obtained. In addition, a new criterion index is presented to quantifiably measure the effectiveness of the seismic isolation of FPB-isolated bridges with different pier heights, which is beneficial to the further popularization and application of FPB in the seismic design of bridge engineering.